Deaf like me - Callner, Jim ([S.l.] : Barr Films [production company] ; Hong Kong : Educational Film Services [distributor], 1981)
Shows how a young girl, whose hearing is severely impaired, is helped to accept herself and to realize the possibilities open to her through a performance of a deaf professional mime, who visits her school. Designed to help hearing children develop empathy for those who are deaf
Title from title screen
Copy available in DVD format
VHS format
Keywords: Deaf children; Deafness in children; Deafness